But why can't I? a book about rules - Graves, Sue; Guicciardini, Desideria (London Franklin watts, 2014)
George thinks rules are silly. When Jenny comes to babysit, George refuses to keep to the rules. But that makes playing dangerous and not fun at all! Can George learn why rules are important? This series introduces young children to different aspects of our emotions and behaviour. A fictional story is backed up by suggestions for activities and ideas to talk about, while a wordless storyboard encourages children to tell another story
Education
Keywords: Educational psychology